Prevalence of Balantidium coli in cattle and cattle breeders in some regions of Baghdad in Iraq - Hussin, AG; Al-Samarai, FR (Bangladesh Journal of Animal Science, 2016)
A study was carried out to determine the prevalence of Balantidium coli infection in cattle and their breeders and related risk factors including the gender, age and region. A total of 200 cattle faecal samples were collected from different ages, sexes and regions of Baghdad (Hor-rageb, Abu Ghraib, AL-Jaderiya, AL-Makaseb, AL-Dowanem and AL-Hamdaniaa) and 88 breeder faecal samples from AL-Makaseb, AL-Dowanem and AL-Hamdaniaa during the period from November 2014 to May 2015. The results showed that the prevalence of Balantidium coli were 29.50% and 9.09% in cattle and their breeders, respectively. The association between infection and all studied factors was not significant except between infection and regions in cattle which were significant (P<0.01). Based on the results of this research, it can be concluded that cattle are highly susceptible to balantidiasis irrespective of sex and age. Bang. J. Anim. Sci. 2016. 45 (2): 30-34